Partisipasi Masyarakat dalam Penerapan Smart Village - Purnamasari, Irma; Raswono, Yudi Mandega; Waeno, Mahamadaree; Samudera, Azhari Azis; Suradika, Agus (Jurnal Governansi, 2025)
The development of digital technology has provided a great opportunity to improve village governance through the concept of smart village. Smart village is an approach to utilizing information technology to support sustainable development in rural areas. The success of this program is not only determined by technological infrastructure, but also by community participation in planning, implementing and evaluating the program. However, community participation in its implementation is still low. Some of the main obstacles include the lack of community understanding of technology, minimal access to information, and busyness and time constraints. This study aims to analyze the level of community participation in the implementation of smart villages and the factors that influence community participation. This study uses a descriptive analysis method with voluntary sampling. The results of the study show that community participation in the implementation of smart villages has not been implemented optimally, this is evidenced by the low values of several indicators, namely community participation in local policy meetings, realization of social participation and evaluation participation. Thus, to support the implementation of smart villages in Bumbung Sembalun Village, a strategy is needed to overcome barriers to participation, including increasing accessibility, incentives, and community-based approaches.